Design and Optimization of a Droop Controller to Fix the Frequency of a Microgrid System Using the Gray wolf Algorithm with Stability Analysis - Zhi Yuan; Ji Li (Advances in Engineering and Intelligence Systems)
Switching between grid-connected and islanded mode, as well as connection and broadcast performance in distributed resources and loads have recently raised many concerns. For this problem, Droop control seems to be a very good solution. On the other hand, load changes cause disruptions in the dynamic behavior and grid behavior, which requires the use of an optimal control strategy to solve it. In order to fix the grid frequency in the presence of consumer load disturbances, this paper presents an optimal droop control strategy. First, a small signal model is extracted for a microgrid in the presence of controllers, consumers, producers and other components. Then, using the gray wolf optimization algorithm, the parameters of the microgrid, including the Droop control parameters, are optimized. Finally, the whole closed-loop system is checked for stability in the presence of optimal parameters. The results show that the optimal control method presented in this article is able to protect the microgrid against frequency changes caused by load changes and fluctuations. The parameters and coefficients of the controllers of the desired control method in this article have been optimized in a way that increases its performance as much as possible. In order to check the performance of the proposed method, a series of simulations are performed in the presence of load disturbances for the entire closed-loop system. The simulation results show the effective performance of the proposed optimal method, which can be used to keep the grid frequency stable in the presence of load disturbances.